Native mobile development a cross-reference for iOS and Android - Lewis, Shaun; Dunn, Mike (O'Reilly, 2019)
"Learn how to make mobile native app development easier. If your team frequently works with both iOS and Android--or plans to transition from one to the other--this hands-on guide shows you how to perform the most common development tasks in each platform. Want to learn how to make network connections in iOS? Or how to work with a database in Android? This book has you covered. In the book's first part, authors Shaun Lewis and Mike Dunn from O'Reilly's mobile engineering group provide a list of common, platform-agnostic tasks. The second part helps you create a bare-bones app in each platform, using the techniques from part one."--Amazon.com
Keywords: Application software / Development; Mobile apps; iOS (Electronic resource); Android (Electronic resource); Mobile computing